A further strange Archaeorthoptera from the Moscovian of Nord-Pas-de-Calais (France) (Insecta, Polyneoptera) - Nel, Andre; Roques, Patrick; Duquesne, Herve (Zootaxa, 2021)
The new Archaeorthoptera Duquesnia gallica gen. et sp. nov. Nel & Roques, is described from the upper Carboniferous of Northern France. It shows several putative synapomorphies with the three genera Contracladus Dvořák et al., 2021 (Pennsylvanian of Germany), Nugonioneura (lower Permian of USA), and Avionugonioneura from the Moscovian of Avion (France).